Organizational Citizenship Behavior in The Creative Industry Sector: Affecting Factors Investigation - Triono, Doni; Suhud, Usep; M, Saparuddin (Journal of Social Science, 2023)
This study aims to examine religiosity, spirituality, and paternalistic leadership's direct influence on Organizational Citizenship Behavior (OCB) or through job satisfaction variables in the Creative Industry sector in Indonesia. This research can be categorized as explanatory research. This research was conducted in Indonesia's creative industry, divided into 16 business fields with a total sample of 406 employees. This study found that religiosity, spirituality, and paternalistic leadership positively and significantly affect OCB. However, suppose through the moderating variable of job satisfaction, the correlation coefficient is smaller than the direct correlation coefficient. In that case, it can be concluded that job satisfaction is not an appropriate moderating variable for the variable religiosity, spirituality, and paternalistic leadership towards OCB. From this study, we can conclude that religiosity, spirituality, paternalistic leadership, and job satisfaction in employees and organizational leaders need to be improved because they are proven to affect OCB directly. Thus, it will also affect individual and organizational performance.